High resolution ion chamber array delivery quality assurance for robotic radiosurgery: Commissioning and validation. Issue 6 (June 2016) - Blanck, Oliver; Masi, Laura; Chan, Mark K.H.; Adamczyk, Sebastian; Albrecht, Christian; Damme, Marie-Christin; Loutfi-Krauss, Britta; Alraun, Manfred; Fehr, Roman; Ramm, Ulla; Siebert, Frank-Andre; Stelljes, Tenzin Sonam; et al.
Highlights: We present a new array-based approach to delivery QA for high precision radiosurgery. We provide test scenarios for delivery QA commissioning for robotic radiosurgery. Our results demonstrate that array-based delivery QA can be used in clinical routine. Our methods and test scenarios demonstrate the detectability of small errors. Abstract: Purpose: High precision radiosurgery demands comprehensive delivery-quality-assurance techniques. The use of a liquid-filled ion-chamber-array for robotic-radiosurgery delivery-quality-assurance was investigated and validated using several test scenarios and routine patient plans. Methods and material: Preliminary evaluation consisted of beam profile validation and analysis of source–detector-distance and beam-incidence-angle response dependence. The delivery-quality-assurance analysis is performed in four steps: (1) Array-to-plan registration, (2) Evaluation with standard Gamma-Index criteria (local-dose-difference ⩽ 2%, distance-to-agreement ⩽ 2 mm, pass-rate ⩾ 90%), (3) Dose profile alignment and dose distribution shift until maximum pass-rate is found, and (4) Final evaluation with 1 mm distance-to-agreement criterion. Test scenarios consisted of intended phantom misalignments, dose miscalibrations, and undelivered Monitor Units. Preliminary method validation was performed on 55 clinical plans in five institutions. Results: The 1000SRS profile measurements showed sufficient agreement compared with a microDiamond detector for all collimator sizes. The relative response changes can be up to 2.2% per 10 cm source–detector-distance change, but remains within 1% for the clinically relevant source–detector-distance range. Planned and measured dose under different beam-incidence-angles showed deviations below 1% for angles between 0° and 80°. Small-intended errors were detected by 1 mm distance-to-agreement criterion while 2 mm criteria failed to reveal some of these deviations. All analyzed delivery-quality-assurance clinical patient plans were within our tight tolerance criteria. Conclusion: We demonstrated that a high-resolution liquid-filled ion-chamber-array can be suitable for robotic radiosurgery delivery-quality-assurance and that small errors can be detected with tight distance-to-agreement criterion. Further improvement may come from beam specific correction for incidence angle and source–detector-distance response.